The effectiveness of a rational counseling program to reduce the risks of modern technology to cognitive processes among a sample of students from the College of Education, Majmaah University - Alhessa, Eman Abdullah (Journal of Educational and Psychological Sciences, 2020)
The current study aimed to identify the effectiveness of a rational counseling program to reduce the risks of modern technology on cognitive processes among a sample of students from the College of Education at Majmaah University. (20) Female students were chosen by the intentional sample method from female college students registered in the mental health course, and they were divided into two experimental groups, one of which consisted of (10) female students, and the other was control and consisted of (10) female students. The study found that: There is clear effectiveness of the rational indicative program to reduce the risks of modern technology on cognitive processes in the sample, and there are differences between the mean of the members of the experimental group, where they obtained a total average (16.40 out of 20), while the control group got the post- measurement (7.50, out of 20) On identifying cognitive processes after applying the rational indicative program in favor of the experimental group. There were no differences between the means of the experimental group in the two dimensional and sequential measurements two months after the application of the program.